Contribution of viscoelastic flow in earthquake cycles within the lithosphere-asthenosphere system - Lambert, Valère (2017)
Faults slip relaxes lithospheric stress imposed by mantle flow and in turn transfers stress to the ductile regions. The interplay of these systems governs the style of deformation at plate boundaries including the recurrence of seismic events. However, such deep processes remain challenging to incorporate in numerical simulations of earthquake cycles. Here we propose a model that couples fault slip and viscoelastic deformation to simulate fault dynamics in the lithosphere-asthenosphere system. Our method resolves all phases of the earthquake cycle, including dynamic rupture propagation, afterslip, slow-slip events, and the modulation of strain rate incurred in the ductile regions. Transient strain accelerations in the asthenosphere may follow both earthquakes and slow-slip events shortly after the rupture, depending on the rheology of the upper mantle and the magnitude of the event. This study opens the door to greater insight into the variability of earthquake cycles by incorporating the dynamics of distributed deformation.